Employee Performance of Life Insurance Companies:The Mediating Effect of Organizational Citizenship Behavior - Suhardi Suhardi; Djoko Soelistya; Retno Purwani Setyaningrum; Nur Aisyah; Nora Pitri Nainggolan (Journal of Economics, Business, and Accountancy Ventura, 2021)
This  study  aims to determine the impact  of  employee  leadership  and  team  member exchange through organizational citizenship behaviour on the employee performance of  foreign  life  insurances.  This  research  uses  the  purposive  sampling  method  for selection.  One hundred  sixty  respondents  are  participating  in the  research used to test the model studied. The data is collected using a questionnaire and then analyzed using the SEM AMOS program. This study showed that servant leadership positively affects  organizational  citizenship  behavior,  team  member  exchange,  and  employee performance. While team member exchange has a positive and significant impact on organizational  citizenship  behavior,  team  member  exchange  has  a  negative  and significant effect on employee performance. Subsequently, organizational citizenship behavior positively and significantly impacts employee performance. The mediating effect  indicated  that  team  member  exchange  and  servant  leadership  influence organizational  citizenship  behavior  and  affect  employee  performance.  The  study's results  imply  that  when  employees  perform  beyond  their  jobs  (organizational citizenship behavior roles) and engage in team member exchange, they have quality social  communication  with  the  workgroup  members.  Additionally,  employees  who work under servant leadership can develop strong personal bonds. Employees with low  levels  of  autonomy  in  their  work  can  improve  performance  if  mediated  by organizational citizenship behavior.